The Complete Project Manager's Toolkit - Englund, Randall; Bucero, Alfonso (Berrett-Koehler Publishers, 2012)
Here Are the Tools to Achieve Project Management Success Buy both The Complete Project Manager and The Complete Project Manager's Toolkit and save $18 at checkout by entering coupon code COMBO1. This companion to The Complete Project Manager provides the tools you need to integrate key people, organizational, and technical skills. The core book establishes that success in any environment depends largely upon completing successful projects; this book gives you the means and methods to meet that goal. The hands-on, action-oriented tools in this book will help you develop a complete set of skills--the right set for you to excel in today's competitive environment. The Complete Project Manager's Toolkit will enable you to implement the easy-to-understand, universal, powerful, and immediately applicable concepts presented in The Complete Project Manager. You may already be aware of what you need to do; this book supplies the how through: " Assessments " Checklists " Exercises " Examples of real people applying the concepts. Use these tested methods to overcome environmental, personal, social, organizational, and business barriers to successful project management! Although The Complete Project Manager can be used as a stand-alone book, it is designed to complement The Complete Project Manager: Integrating People, Organizational, and Technical Skills